2021
DOI: 10.1097/md.0000000000026298
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study on severe acute respiratory syndrome coronavirus 2 virus transmission network in northeast China

Abstract: In this study, corona virus disease 2019 (COVID-19) transmission networks were built to analyze the epidemic situation of COVID-19 in Liaoning and Jilin provinces in early 2020. We explore the characteristics of the spread of COVID-19, and put forward effective recommendations for epidemic prevention and control. We collected demographic characteristics, exposure history, and course of action of COVID-19 cases. We described the demographic and case characteristics of these cases to show the basic characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Positive correlations were observed between Omicron morbidity and income support, workplace closures, and containment index. Feng et al 21 found that the number of confirmed cases was positively correlated with gross domestic product in LiaoNing and Jilin, China. Marcos César Ferreira also found that the population most vulnerable to COVID‐19 were those living in the districts with lower salaries and slum areas in the São Paulo municipality, Brazil 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive correlations were observed between Omicron morbidity and income support, workplace closures, and containment index. Feng et al 21 found that the number of confirmed cases was positively correlated with gross domestic product in LiaoNing and Jilin, China. Marcos César Ferreira also found that the population most vulnerable to COVID‐19 were those living in the districts with lower salaries and slum areas in the São Paulo municipality, Brazil 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Feng et al 21 found that the number of confirmed cases was positively correlated with gross domestic product in LiaoNing and Jilin, China.…”
Section: Multiple Linear Regressionmentioning
confidence: 99%